Literature About Islam in America: A Survey of Source of Information by Muhammad Tahir and Siddiq ‘Ali (American Journal of Islam and Society, 1987)
Information explosion is a modern phenomenon. This explosion can beseen in all areas of knowledge. In an attempt to keep track of this growth,secondary sources of information have also mushroomed. Each subject fieldhas its own secondary sources of information. For instance, art has Art Index,education has Education Index, library science has Library Literature.Despite these developments in indexing, and despite the progress in interdisciplinarystudies, internationally in general and American in particular,literature on Islam and Muslims rarely gets the place it deserves. Sources ofseeondaq information should be scanned to determine how far they cover informationon Islam and Muslims. This would help us to understand the importancegiven to Islam and Muslims by American writers.A scholar looking for sources of infannation on Islam in the United Statesis bound to be disappointed. It is surprising that no exhaustive attempt has asyet been made to gather information on Islam in one place. This despite thefact that Islam has emerged as one of the important religions followed by asubstantial number of Americans. In addition, the emergence of the Arab andGulf nations as important centres of economic power in the world has ledmany Americans to take an interest in Islam and Muslims. As against theneglect by the Americans, the Eumpeans have come out with an index ofIslamic literature in European languages entitled Index Islamicus. This comprehensivework finds no parallel anywhere in the world.As no attempt has been made yet to bring together all the informationabout Islam available in the United States, it is necessary to look deep intoevery book, journal, newspaper, film, and tape, etc. It is both surprising andshocking to note a sordid treatment meted out to literature on Islamic Studies.The population of Muslims in the United States is not so negligible as to warrantsuch a stepmotherly treatment at the hands of those who are at the helm of ...